2022
DOI: 10.3390/bioengineering9110676
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study to Evaluate the Wear Performance of UHMWPE and XLPE Material for Orthopedics Application

Abstract: The main objective of this study is to perform an abrasive wear resistance study of UMHWPE and XLPE by using different grades of abrasive paper (grade 100 (190 µm), grade 220 (50 µm), and grade 400 (40 µm)) with minor (10 N) and major (15 N) loading conditions. In this article, wear performance of the UMHWPE and XLPE materials compared to the bio-tribological data as reported earlier in the clinical studies has been investigated. The experimental result shows that the loss of materials for the XLPE was much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The study here is an attempt to give an overview and provide broad coverage of the working of these systems and their value in the research, clinic and at home. In recent years researchers have studied different aspects of human bones using advanced biomaterials with FEA and experimental techniques [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The study here is an attempt to give an overview and provide broad coverage of the working of these systems and their value in the research, clinic and at home. In recent years researchers have studied different aspects of human bones using advanced biomaterials with FEA and experimental techniques [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…When subjected to light loads, cross-linked polyethylene (XLPE) maintains its wear resistance, making it suitable for use as a support for internal fixation devices, including screws, plates, and pins. As reported by Bhoi et al [41], UMHWPE and XLPE underwent abrasive wear resistance testing using three paper grades of increasing abrasiveness (grade 100 (190 µm), grade 220 (50 µm), and grade 400 (40 µm)), under low (10 N) and high (15 N) loading conditions. The testing results demonstrated that XLPE was more wear-resistant under moderate loads and fine grit sandpaper, while UHMWPE performed better under heavy loads and coarse grit sandpaper.…”
Section: Uhmwpe For Biomedical Applicationsmentioning
confidence: 96%
“…A comprehension of the operation of natural joints has served as a catalyst for the creation of biomimetic medical implant solutions. The utilisation of bio-tribological principles is particularly significant when it comes to medical implants, as the reduction of attrition, enhancement of lubrication, and guarantee of biocompatibility are of the utmost importance [10][11][12][13][14].This review provides a detailed analysis of recent advancements in bio-tribology, focusing on medical implant tribology and joint lubrication. It synthesizes data from various research initiatives to offer a comprehensive outlook on the field's current state.…”
Section: Introductionmentioning
confidence: 99%